PENGEMBANGAN BAHAN AJAR BERBASIS KEARIFAN LOKAL PROVINSI SUMATERA UTARA PADA MATERI KERAGAMAN BUDAYA UNTUK MENUMBUHKAN RASA CINTA TANAH AIR DI KELAS IV SD - Wanda Viola Sapinka; Hasanah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to (1) analyze the feasibility of teaching materials based on local wisdom in the province of North Sumatra, (2) analyze the practicality of teaching materials based on local wisdom in the province of North Sumatra for class teachers and (3) analyze student responses to teaching materials based on local wisdom in the province of Sumatra developed north. This research is a type of research and development using the ADDIE development model. This research used five stages. (1) analysis stage, namely curriculum analysis and material analysis, (2) design stage, namely designing products that suit needs. (3) development stage. (4) implementation stage, and (5) evaluation stage. writing teaching materials that are appropriate to the material. The subjects in this research were expert validators of teaching materials, class teachers and students. The instrument used to collect data is a questionnaire. The data analysis technique in this research is quantitative descriptive. Based on the results of data analysis obtained through the expert validation test of teaching materials I, 88% was obtained in the